Effects of Fall vs. Spring Plowing Forages on Nitrate Leaching Losses to Groundwater. Issue 1 (12th December 2014) - Jiang, Yefang; Jamieson, Terra; Nyiraneza, Judith; Somers, George; Thompson, Barry; Murray, Brian; Grimmett, Mark; Geng, Xiaoyuan
Abstract: High levels of nitrate leaching losses from potato rotation systems have caused concerns for both drinking water quality and aquatic ecosystem protection in Prince Edward Island (PEI). Paired‐field experiments were carried out in commercial fields to evaluate the potential of delayed plowing forages within potato rotation from fall to spring on reducing nitrate leaching at two separate sites in PEI during 2010 and 2013. Monitoring showed that fall plowing resulted in elevated tile‐drain nitrate concentrations compared to spring plowing, probably mainly due to crop residue mineralization during fall which was hastened by earlier herbicidal termination of forage (i.e., herbicidal killing) at Site 1. A similar trend was also observed regarding nitrate concentrations of shallow groundwater at Site 2 during the forage phase. The practice of delaying the plowing of forages and/or associated earlier herbicidal termination of forage until spring reduces forage‐phase nitrate leaching loss by 20 to 61%, and should therefore be encouraged for nitrate mitigation. The study also demonstrated that only a small fraction (9.6 to 22%) of the fall plow‐down forages decayed during the forage phase and a large portion was retained in the soil into the next season. Growers should consider accounting for some of the carried‐over N for the subsequent crops regardless implementing fall or spring plowing.